Intelligence in Communication Systems c - Glitho, Roch.; Karmouch, Ahmed; Pierre, Samuel; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
International Federation for Information Processing The IFIP series publishes state-of-the-art results in the sciences and technologies of information and communication. The scope of the series includes: foundations of computer science; software theory and practice; education; computer applications in technology; communication systems; systems modeling and optimization; information systems; computers and society; computer systems technology; security and protection in information processing systems; artificial intelligence; and human-computer interaction. Proceedings and post-proceedings of referred international conferences in computer science and interdisciplinary fields are featured. These results often precede journal publication and represent the most current research. The principal aim of the IFIP series is to encourage education and the dissemination and exchange of information about all aspects of computing. For more information about the 300 other books in the IFIP series, please visit springeronline.com. For more information about IFIP, please visit www.ifip.org.
A Framework for Building Customized Adaptation Proxies -- Adaptable Services and Applications for Networks -- Improvement of MPLS Performance by Implementation of a Multi-Agent System -- Enabling Mobile Commerce Through Location Based Services -- Inter-Domain Traffic Engineering Using Mpls -- Autonomic Service Configuration by a Combined State Machine and Reasoning Engine Based Actor -- Self-Management in Ambient Networks for Service Composition -- Amapola: A Simple Infrastructure for Ubiquitous Computing -- Decoupling Components of an Attack Prevention System Using Publish/Subscribe -- A P2P Collaborative Framework for Smartphone -- Dynamic Role Binding in a Service Oriented Architecture -- Formal Modelling of an Adaptable Service System -- A Localized Architecture for Detecting Denial of Service (DoS) Attacks in Wireless AD Hoc Networks -- A Fuzzy Petri Nets QoS Model for Wireless AD Hoc Networks -- Using Mobile Agent for Location-Specific Data Retrieval in Manet -- Optimization of Handover Performance for Fmipv6 -- XML Access Control for Security and Memory Management -- Approximating Saml Using Similarity Based Imprecision -- A Distributed Proxy Architecture for Service Discovery in Peer-to-Peer Networks -- Directional Antenna Based Performance Evaluation of 802.11 Wireless Local Area Networks -- Service-Driven Group Management for Mobile P2P Services -- Towards Programmable Context-Aware Voice Services -- Context-Aware Security Policy Agent for Mobile Internet Services -- Colos -A System for Device Unaware and Position Dependent Communication Based on the Session Initiation Protocol -- A Key-Exchanging Scheme for Distributed Sensor Networks -- A Look Into the 4G Crystal Ball -- Discovering Architecture Formalism of Geo-Located Web Services for Next Generation of Mobile Networks.
Keywords: Computer science; Computer communication systems; Computers; Artificial intelligence; Electrical engineering; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Communications Engineering, Networks; Information Systems and Communication Service; Electronic books